THE EFFECT OF PRICE, EXCHANGE RATE, AND CONSUMPTION ON INDONESIAN RUBBER EXPORTS BY MAIN DESTINATION COUNTRY - Lisdiani, Ilfy; Nikensari, Sri Indah; Iranto, Dicky (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
As one of the largest natural rubber exporters in the world, Indonesia has global potential to conquer therubber export market. This condition is indicated by the high value of Indonesia's natural rubber exportsto the global market. Based on the current world natural rubber export data of 64.8%, this value is ofcourse controlled by the world's two largest rubber exporters, one of which is Indonesia at 28.8%. Thisstudy aims to determine the effect of prices, exchange rates, and consumption on Indonesian rubberexports according to the main destination countries. The method used in this study is the panel dataregression method of the five main destination countries for Indonesian rubber exports, namely theUnited States, Japan, China, India, and South Korea in the 2013-2019 period with a fixeffect model.This data is secondary data obtained through a trade map and world bank and processed usingEviews 11. The results show that the variables of price, exchange rate, and consumption have asignificant and positive effect on rubber exports in Indonesia by destination country.